Synthesis, spectral characterisation and antimicrobial properties of Cu(II) and Fe(II) complexes with xanthone / Rabuyah Ni, Mohammad Isa Mohamadin and Vivien Yi Mian Jong - Ni, Rabuyah; Mohamadin, Mohammad Isa; Mian Jong, Vivien Yi (Universiti Teknologi MARA Shah Alam, 2017)
The new complexes [CuL2(H2O)2] and [FeL2(CH3O)2] in which L = β-mangostin were synthesised and characterised. The structure of the ligand, β-mangostin was confirmed using NMR and the purity of ligand was determined using HPLC. Both Cu(II) and Fe(II) complexes were prepared by reaction between the ligand and the acetate of the metals in one-step reaction. The synthesised compounds have been characterised using UV-Visible, FTIR and CHNS analyser. Ligand and metal complexes were tested against bacteria to assess on their antimicrobial properties using Minimum Inhibitory Concentrations (MICs) and Minimum Bactericidal Concentrations (MBCs) method. The elemental analysis and spectra data suggested octahedral geometry for both Cu(II) and Fe(II) complexes. The IR spectroscopy revealed that the chelation of Cu2+ and Fe2+ ion occurred with hydroxyl and carbonyl group at C9 and C1 respectively of β-mangostin. Both Cu(II) and Fe(II) complexes showed stronger inhibition against Pseudomonas aeruginosa, Proteus vulgaris, Klebsiella pneumoniae and Salmonella pneumonia at concentration 900 mg/mL and Escherichia coli at 450 mg/mL compared to the ligand itself.